Effect of Arbidol (Umifenovir) on COVID-19: a randomized controlled trial - Nojomi, Marzieh; Yassin, Zeynab; Keyvani, Hossein; Makiani, Mahin Jamshidi; Roham, Maryam; Laali, Azadeh; Dehghan, Nasir; Navaei, Mehrnaz; Ranjbar, Mitra (BMC infectious diseases, 2020)
Treatment of patients with COVID-19 has included supportive care to mainly relief symptoms of the disease. Although World Health Organization (WHO) has not recommended any effective treatments for COVID-19, there are some reports about use of antiviral drugs. The aim of this study is to determine the effect of Arbidol (ARB) on COVID-19 disease. Using an open-label randomized controlled trial, we examined the efficacy of ARB in patients with COVID-19 in a teaching hospital. One hundred eligible patients with diagnosis of COVID-19 were recruited in the study and assigned randomly to two groups of either hydroxychloroquine followed by KALETRA (Lopinavir/ritonavir) or hydroxychloroquine followed by ARB. The primary outcome was hospitalization duration and clinical improvement 7 days after admission. The criteria of improvement were relief of cough, dyspnea, and fever. Time to relief from fever was also assessed across the two groups. Without any dropouts, 100 patients were entered into the study for the final analysis at significance level of 0.05. The mean age of patients was 56.6 (17.8) years and 56.2 (14.8) years in ARB and KALETRA groups, respectively. Majority of patients were male across two groups (66 and 54%). The duration of hospitalization in ARB group was significantly less than KALETRA arm (7.2 versus 9.6 days; P = 0.02). Time to relief fever was almost similar across two groups (2.7 versus 3.1 days in ARB and KALETRA arms, respectively). Peripheral oxygen saturation rate was significantly different after 7 days of admission across two groups (94% versus 92% in ARB and KALETRA groups respectively) (P = 0.02). Based on multiple linear regression analysis, IHD, Na level, and oxygen saturation at the time of admission and type of therapy were the independent adjusted variables that determined the duration of hospitalization in patients with COVID-19. Our findings showed that Arbidol, compared to KALETRA, significantly contributes to clinical and laboratory improvements, including peripheral oxygen saturation, requiring ICU admissions, duration of hospitalization, chest CT involvements, WBC, and ESR. We suggest further studies on ARB against COVID-19 using larger sample size and multicenter design. IRCT20180725040596N2 on 18 April 2020.